Problems of Islamic Education in The Era of Industrial Revolution 4.0 - Raodatul Jannah (Journal of Social Science, 2022)
The existence of Islamic education in Indonesia has been around for a long time since the 13th century AD, but various problems have always accompanied Islamic education from the colonial colonial era, the Old Order, the New Order, Reformation, to the Industrial Revolution Era 4.0. especially in the midst of this era of industrialization, forcing all elements within the State and society based on digitalization and manufacturing. This is very much different from the paradigm of Islamic education which focuses on guiding humans so that they become Islamic-spiritual human beings who must be oriented towards technology and manufacturing. There are a number of problems that are still the "blockstone" of Islamic education in the midst of this rapid flow of industrialization, namely: First, there is still a dichotomy of science (between general science and religious knowledge); Second, the research culture in Islamic educational institutions is still weak (both scholars, practitioners, policy makers, and the openness of educational institutions such as Islamic boarding schools and madrasas, each of which considers research to be a Western product); Third, curriculum problems that often change along with changes in the minister of education; Fourth, limited human resources in terms of quantity and quality (both teachers, lecturers, tutors, ustadz, and others); Fifth, the Islamic education management system is still not well organized; mastery of science and ICT in the administration of education, and; Sixth, the education evaluation system which so far still relies on national exam scores. The research conducted by the author is a field research with a qualitative description.